2016
DOI: 10.1021/acs.est.6b01243
|View full text |Cite
|
Sign up to set email alerts
|

High-Content and Semi-Automated Quantification of Responses to Estrogenic Chemicals Using a Novel Translucent Transgenic Zebrafish

Abstract: Rapid embryogenesis, together with genetic similarities with mammals, and the desire to reduce mammalian testing, are major incentives for using the zebrafish model in chemical screening and testing. Transgenic zebrafish, engineered for identifying target gene expression through expression of fluorophores, have considerable potential for both high-content and high-throughput testing of chemicals for endocrine activity. Here we generated an estrogen responsive transgenic zebrafish model in a pigment-free "Caspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…50 This translucent model extends the use of fluorescent reporters to life-stages >5 dpf, which would otherwise gain skin pigmentation that interferes with GFP detection. 48 This is an important feature of the model, as EDC effects may vary both within a tissue and between body tissues at different life-stages. 4,51,52 The life-stages selected for this study represent two key landmarks in CV development: 5 days post fertilization (dpf) marking formation of the endocardial rings (precursors to the heart valve leaflets); 15 dpf marking elongation of the valve leaflets.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 This translucent model extends the use of fluorescent reporters to life-stages >5 dpf, which would otherwise gain skin pigmentation that interferes with GFP detection. 48 This is an important feature of the model, as EDC effects may vary both within a tissue and between body tissues at different life-stages. 4,51,52 The life-stages selected for this study represent two key landmarks in CV development: 5 days post fertilization (dpf) marking formation of the endocardial rings (precursors to the heart valve leaflets); 15 dpf marking elongation of the valve leaflets.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…39,71,72 Both lower and 10× higher (worst case) BPA concentrations were substantially below maximum tolerable concentrations. 48 MBP exposure concentrations were based on a relative potency of 250× compared to BPA, measured in vivo in juvenile medaka. 43 Stock solutions were prepared by dissolving pure test chemicals in analytical grade dimethyl sulfoxide (DMSO) and then diluting (200× ) in 400 mL of embryo culture water 73 to give the desired nominal exposure concentrations in 0.5% DMSO.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…( a ) Comparative graph showing EC50s from different endocrine-disrupting studies in small fish in early and late stages [9,16,17,18,19,23,27,29,34,35,40,42,59,60,61,62,63,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79] Compounds not previously tested by others are excluded. Details for each study are shown in Table S4.…”
Section: Figurementioning
confidence: 99%
“…All of them rely, among other parameters, on the quantification of plasma sex-specific proteins (vitellogenin and spiggin) after at least 21 days of exposure, belonging therefore to the category of animal testing. Within the early stages, most of the efforts so far have been focused on the validation and use of gene expression markers to assess estrogenicity [16] and the subsequent construction of specific transgenic lines combining estrogenic responsive promoters and fluorescent reporter genes [17,18]. Surprisingly, additional endocrine axes such as androgens and thyroid have been widely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Biosensor transgenic fish offer great potential for both mixture and temporal effects analyses for exposure to chemicals and their mixtures (34)(35)(36). Here we applied an Estrogen Responsive Element (ERE) -Green Fluorescent Protein (GFP) transgenic zebrafish (Danio rerio) model in a pigment free (Casper) strain of zebrafish [ERE-GFP-Casper; (37)] to investigate for health effects and life stage sensitivities following chronic and acute exposures to a WwTW effluent with known (measured) estrogenic content. The responses measured included assessments on survivorship, growth, sex and sexual development (via gonadal histopathology), fluorescence induction in both target tissues (via fluorescence microscopy) and in whole bodies via quantification of gfp mRNA (via qRT-PCR).…”
Section: Introductionmentioning
confidence: 99%